2008
DOI: 10.1677/joe-07-0491
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue loss in adjuvant arthritis is associated with a decrease in lipogenesis, but not with an increase in lipolysis

Abstract: Adjuvant-induced arthritis is a model of rheumatoid arthritis that induces cachexia. In other cachectic situations, there is an increase in lipolysis resulting in a loss of adipose tissue mass. The aim of this work was to analyse the effect of chronic arthritis, induced by adjuvant injection, on white adipose tissue (WAT). For this purpose, rats were killed 10 days after adjuvant injection, when the first external symptoms appeared, on days 15 and 22 when the external signs of the illness reach their severest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 49 publications
(45 reference statements)
6
33
0
Order By: Relevance
“…Our result on the reduction of circulating adiponectin levels during AA confirm the recent finding of Haruna et al (2007), Martin et al (2008), and our own observation (Stofkova et al 2009) in the clinical phase of AA, and suggests that this may be involved in the downregulation of GLUT4 in adipocytes. Any interpretation of reduced adiponectin plasma levels related to the severity of the disease can not be drawn, because the decisive role plays its intraarticular production.…”
Section: Discussionsupporting
confidence: 92%
“…Our result on the reduction of circulating adiponectin levels during AA confirm the recent finding of Haruna et al (2007), Martin et al (2008), and our own observation (Stofkova et al 2009) in the clinical phase of AA, and suggests that this may be involved in the downregulation of GLUT4 in adipocytes. Any interpretation of reduced adiponectin plasma levels related to the severity of the disease can not be drawn, because the decisive role plays its intraarticular production.…”
Section: Discussionsupporting
confidence: 92%
“…Muscle wasting is associated with an increase in myostatin in cancer (10), whereas no modification in myostatin was observed in the skeletal muscle of arthritic rats. Furthermore, fat mass loss in arthritis is associated with a decrease in adipogenesis rather than an increase in lipolysis (31). On the other hand, in cancer, lipolysis is induced by an increase in zinc-␣ 2 -glycoprotein (ZAG), which plays an important role in loss of fat mass (4), whereas ZAG expression is not modified in arthritic rats (31).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fat mass loss in arthritis is associated with a decrease in adipogenesis rather than an increase in lipolysis (31). On the other hand, in cancer, lipolysis is induced by an increase in zinc-␣ 2 -glycoprotein (ZAG), which plays an important role in loss of fat mass (4), whereas ZAG expression is not modified in arthritic rats (31). In cancer cachexia, EPA Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin comes mainly from adipose cells. Most studies have found significantly elevated serum levels of leptin in RA patients [7,18,22,[26][27][28]30,36,40,92,93], while others have found decreased levels [19,21,32,34]. Although the relationship is complex, leptin has been shown to be the major factor linkage of food intake with bone metabolism [94].…”
Section: Leptin and Rheumatoid Arthritismentioning
confidence: 99%